2014
DOI: 10.1590/s1516-635x2014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the profitability of organic and conventional broiler production

Abstract: Recently, organic broiler chicken production has received more attention worldwide. This study has carried out an economic analysis to compare the profitability of organic versus conventional growing systems per unit of broiler meat production. To achieve this goal, 400 slow-growing broiler chickens (Hubbard Red-JA) were reared in an organic production system, and the same number of fast-growing birds (Ross-308) in a conventional system. The profitability was deduced with an economic analysis that compared tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Organic poultry have access to pasture [6,39], a nutrient source that has not been completely investigated for use in poultry. Organic poultry production focuses particularly on animal health and wellbeing, good environmental practices, and product quality and focuses less on economic concerns, such as reducing costs and maximizing production [37,50].…”
Section: Organic Systemmentioning
confidence: 99%
“…Organic poultry have access to pasture [6,39], a nutrient source that has not been completely investigated for use in poultry. Organic poultry production focuses particularly on animal health and wellbeing, good environmental practices, and product quality and focuses less on economic concerns, such as reducing costs and maximizing production [37,50].…”
Section: Organic Systemmentioning
confidence: 99%
“… Guarino Amato and Castellini (2022) reported that the organic broiler production system operated according to precise and specific production standards are increasing worldwide. Moreover, demand for organic poultry products, a production system that reduces chemical use and emphasis on animal welfare, has increased as it is perceived to be safer and more nutritious than conventionally raised poultry ( Cobanoglu et al, 2014 ; Niggli, 2015 ). Therefore, the organic-certified broiler production in Korea is also increasing quickly and is expected to continue to grow ( MAFRA, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing the income relative to feed cost, birds were found to have increased body weights and feed conversion rates in this experimental group [ 37 ]. Attention should also be paid to other factors that significantly affect the profitability and efficiency of production, such as the maintenance system [ 38 ], stocking density per 1 m 2 of surface area [ 39 ], and the use of organic acids or phytobiotics [ 40 ].…”
Section: Discussionmentioning
confidence: 99%